PROBABILITY ANALYSIS OF RAINFALL AT AKOLA, MAHARASHTRA - Pimpale, A.R.; Hiwase, S.S.; Patil, P.G. (Journal of Soil and Water Conservation, 2022)
The knowledge of rainfall pattern (amount and probability) helps in planning of crops grown in the region and also in watershed management. Therefore, monthly and annual rainfall data for 29 years (1970-1998) for the station Akola has been collected and its analysis has been attempted. The monthly rainfall data was analyzed for finding out drought, normality and abnormality probability. The analysis indicated that the rainfall is mainly confined to four months of June to September having average annual rainfall of 825.11 1 mm. August is the wettest month (average rain-222.0 mm) and April is driest month (average rain-3.82 mm). August has good regularity of rainfall (C. V 46.0%). Next to August rainfall in July and June is also regular (C.V 47% and 55% respectively) whereas in April and March it is most irregular (C. V 193% and 184%). The S.D. and C. V for annual rainfall were found to be 192.8 Mill and 23.0% respectively.